SEMANTIC ANALYSIS OF THE CONCEPT "TEST" IN ENGLISH AND UZBEK FAIRY TALES - Israilova Sayyora Tashpulotovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article is about the semantic analysis of the concept of "test" in English and Uzbek fairy tales. In English and Uzbek fairy tales, the concept of "testing" is expressed by the person being tested by the test subject in different situations, the protagonist fulfilling various conditions, fighting invincible warriors or defeating an immortal creature, and this is expressed through certain lexical units.